2022
DOI: 10.3847/1538-4357/ac9df4
|View full text |Cite
|
Sign up to set email alerts
|

A Data-constrained Magnetohydrodynamic Simulation of the X1.0 Solar Flare of 2021 October 28

Abstract: The solar active region NOAA 12887 produced a strong X1.0 flare on 2021 October 28, which exhibits X-shaped flare ribbons and a circle-shaped erupting filament. To understand the eruption process with these characteristics, we conducted a data-constrained magnetohydrodynamics simulation using a nonlinear force-free field of the active region about an hour before the flare as the initial condition. Our simulation reproduces the filament eruption observed in the Hα images of GONG and the 304 Å images of SDO/AIA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The event we select is the second GOES X-class flare in solar cycle 25, hosted in NOAA active region 12887, occurring around 15:35 UT on 2021 October 28. This event has been reported by other papers, which focused on some observational features, such as observations of EUV waves and the corresponding CME (Devi et al 2022;Hou et al 2022), the CME three-part structure (Devi et al 2022), the eruption mechanism (Yamasaki et al 2022), the Sun-as-a-star spectroscopic characteristics (Xu et al 2022), the solar energetic particles (Li et al 2022), and the geomagnetic effects (Papaioannou et al 2022). It would be of great interest to check in what degree such a geoeffective solar eruption can be reproduced with a data-driven radiative MHD model.…”
Section: Event Overview and Numerical Setupsupporting
confidence: 64%
See 1 more Smart Citation
“…The event we select is the second GOES X-class flare in solar cycle 25, hosted in NOAA active region 12887, occurring around 15:35 UT on 2021 October 28. This event has been reported by other papers, which focused on some observational features, such as observations of EUV waves and the corresponding CME (Devi et al 2022;Hou et al 2022), the CME three-part structure (Devi et al 2022), the eruption mechanism (Yamasaki et al 2022), the Sun-as-a-star spectroscopic characteristics (Xu et al 2022), the solar energetic particles (Li et al 2022), and the geomagnetic effects (Papaioannou et al 2022). It would be of great interest to check in what degree such a geoeffective solar eruption can be reproduced with a data-driven radiative MHD model.…”
Section: Event Overview and Numerical Setupsupporting
confidence: 64%
“…It is worth pointing out that this event has also been studied by Yamasaki et al (2022) with their zero-β data-constrained simulation, focusing on the eruption mechanism and the reconnection process. Some differences emanate from the comparison between these two models.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that nonpotentiality parameters like shear angle, vertical current, and current helicity exhibited an increasing trend in the NOAA 10486 before X-class flares occurred [6]. Nonetheless, we propose that the collision observed by Yamasaki et al [4] could cause variations in all magnetic nonpotentiality parameters, leading to the instability of NOAA 12887 and initiating the eruption of the X1.0 flare.…”
Section: Introductionmentioning
confidence: 54%
“…The active region NOAA 12887 erupted an X1.0 flare during the early stages of the 25th solar cycle. Yamasaki et al [4], conducted a study of NOAA 12887 with data constrained magnetohydrodynamics simulation using NLFFF and proposed that the intruding motion on October 28th could potentially initiate magnetic reconnection and triggers the X-class flare.…”
Section: Introductionmentioning
confidence: 99%
“…On 2021 October 28, an X1.0 flare took place in NOAA AR12887. As the first X-class flare observed on the disk center in Solar Cycle 25, it has been reported from several points of view (Hou et al 2022;Xu et al 2022;Yamasaki et al 2022). We pay attention to the detailed dynamical evolution of two filaments associated with this large flare and find first some threads wrapping a leg of a filament during its interaction with another one.…”
Section: Introductionmentioning
confidence: 75%